Theoretical and Implementational Problems in Curriculum Development and the Learning Process - syah, Abdurahman; Annur Sofiah (The Future of Education Journal, 2025)
This research examines the theoretical and practical challenges in the development and implementation of the curriculum in Indonesian education. The aim is to analyze these issues and propose reconstructive solutions so that curriculum theory and practice align with the needs of 21st-century education. Using a qualitative approach, this study employs a literature review method with analysis of academic sources, policies, and curriculum documents from 2020 to 2024. The population includes relevant educational literature and policy documents, with purposive sampling based on relevance and credibility. Data collection is conducted through document analysis with systematic coding techniques and thematic categorization, utilizing content analysis. The findings indicate theoretical problems rooted in a crisis of philosophy, epistemology, and axiology, as well as practical issues such as teacher competencies, infrastructure limitations, and top-down policies. The conclusion emphasizes the need for comprehensive curriculum reconstruction that prioritizes relevance, flexibility, and the integration of values and technology to shape character and competencies that meet global needs. Key implications include decentralization of policies, teacher professionalism, and reflective evaluation to enhance the quality and relevance of education.